Aplikasi Zat Pengatur Tumbuh (ZPT) Bawang Merah terhadap Keberhasilan Stek Sirih Merah (Piper crocatum Ruiz): Application of Shallot Plant Growth Regulator (PGR) on the Successful of Red Betel (Piper crocatum Ruiz) Plant Cuttings - F. Silvi Dwi Mentari; Zahrotul Isti'anah Marroh; Ita Merni Patulak; Yuanita; Daryono (Jurnal Loupe, 2026)
This study aims to calculate the growth rate indicated by the emergence of shoots and the percentage of successful growth of red betel cuttings given plant growth regulators (PGR) in the form of shallots. This study used a non-factorial Completely Randomized Design (CRD) with three treatment levels and 30 individual replicates per treatment (90 experimental units in total): the first treatment level was control (no shallot extract), the second treatment level was red betel cuttings soaked in shallot extract at a concentration of 50%, and the third treatment level was red betel cuttings soaked in shallot extract at a concentration of 75%, with a soaking duration of 1 hour. Growth-rate data were analyzed descriptively, while cutting-success data were further tested using a Chi-square test to determine differences among treatments. The results showed that soaking with shallot extract at the third treatment level (75% concentration) increased cutting success up to 100%, with shoots beginning to emerge on the 7th day, and this was statistically different from the control (χ² = 32.58; p < 0.001).